2005
DOI: 10.1007/s10714-005-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

Some remarks on the angular momenta of galaxies, their clusters and superclusters

Abstract: We discuss the relation between angular momenta and masses of galaxy structures base on the Li model of the universe with global rotation. In our previous paper (God lowski et al 2002) it was shown that the model predicts the presence of a minimum in this relation. In the present paper we discuss observational evidence allowing us to verify this relation. We check these theoretical predictions analysing Tully's galaxy grups. We find null angular momentum J = 0 for the masses corresponding to mass of galaxy gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 34 publications
(31 reference statements)
2
30
0
Order By: Relevance
“…We emphasize however, that the above observational results about lack of alignment of galaxies for poor clusters, as well as evidence for such alignment in the rich galaxy clusters (Godłowski, Szydłowski & Flin (2005), Aryal et al (2007), see also Godłowski, 2011 for later improved analysis) clearly shows that angular momentum of galaxy groups and clusters increases with their richness. The problem of clusters angular momenta in context of their mutual interactions as well as those with dark matter haloes has been discussed by Hahn et al (2007) based on the results of computer simulations.…”
Section: Discussionmentioning
confidence: 65%
“…We emphasize however, that the above observational results about lack of alignment of galaxies for poor clusters, as well as evidence for such alignment in the rich galaxy clusters (Godłowski, Szydłowski & Flin (2005), Aryal et al (2007), see also Godłowski, 2011 for later improved analysis) clearly shows that angular momentum of galaxy groups and clusters increases with their richness. The problem of clusters angular momenta in context of their mutual interactions as well as those with dark matter haloes has been discussed by Hahn et al (2007) based on the results of computer simulations.…”
Section: Discussionmentioning
confidence: 65%
“…Godlowski et al (2003) described Li (1988) model and showed the relation between the angular momenta and the masses of the large scale structures. This relationship was observationally tested by several authors (Godlowski et al 2005, Hu et al 2006, Aryal & Saurer 2006, Aryal et al 2007, 2008, Godlowski et al 2010, Godlowski 2012 and found the vanishing angular momenta for less massive structures and non-vanishing for larger structures. Aryal et al (2013) studied preferred alignments of angular momentum vectors of galaxies in six rotating clusters (A954, A1139, A1399, A2162, A2169, and A2366) that are dynamically stable and have a single peak in 1D-3D number density maps.…”
Section: Introductionmentioning
confidence: 94%
“…Godlowski et al (2003) derived a relation between angular momentum and the mass of a galaxy using the "Li model" (Li 1998) and tested this relation for Tully's galaxy group (Godlowski et al 2005). For that group, no preferred alignment of SVs of galaxies is noticed.…”
Section: Discussionmentioning
confidence: 99%